Weight change after antiretroviral therapy initiation among adults living with HIV in Northwest Ethiopia: a longitudinal data analysis. Issue 2 (1st February 2022) - Alebel, Animut; Demant, Daniel; Petrucka, Pammla Margaret; Sibbritt, David
Abstract : Objectives: The first objective was to explore weight change in the first 2 years after antiretroviral therapy (ART) initiation in adults living with HIV. The second objective was to identify the predictors of weight change over time among adults living with HIV on ART. Design: An institution-based retrospective longitudinal study was conducted. Setting: The study was conducted at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia. Participants: The study included 848 randomly selected medical charts of adults living with HIV receiving ART between June 2014 and June 2020. Primary and secondary outcomes: The primary outcome was weight change in the first 2 years after ART initiation. The secondary outcome was to identify predictors of weight change. Association between predictor variables and weight change was assessed using an LMM. Variables with p values <0.05 in the final model were considered as statistically significant predictors of weight change. Results: Of 848 study participants, more than half (n=499; 58.8%) were female. Participants' mean weight increased from 54.2 kg (SD ±9.6 kg) at baseline to 59.5 kg (SD ±10.7 kg) at the end of follow-up. Duration of time on ART, sex, WHO clinical disease staging, functional status, nutritional status and presence of opportunistic infections were significant predictors of weight change at ART initiation. Significant interaction effects were observed between time and sex, WHO clinical disease staging, functional status, isoniazid preventive therapy and nutritional status. Conclusion: We found a linear increment of weight over 24 months of follow-up. Rate of weight gain over time was lower in patients with advanced disease stage and working functional status, whereas weight gain rate was higher in male and underweight patients.